THE INFLUENCE OF ACTIVE LEARNING STRATEGIES ON MATHEMATICS LEARNING MOTIVATION OF FIFTH GRADE STUDENTS OF ELEMENTARY SCHOOL (SD) NAKULA CLUSTER, JEMBRANA SUB-DISTRICT - Dewi, Made Sri Astika; Lestari, Nyoman Ayu Putri (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
This study aims to analyze the differences in learning motivation between students who study using active learning strategies and learning strategies. This type of research is a quasi-experimental (quasi-experimental) with a non-equivalent pretest-posttest control group design. The study population was all fifth graders at State Elementary School 2021/2022, totaling 162 people. The class sample was taken by random sampling technique. The sample consisted of 2 classes, namely Class V SDN 1 Banjar Tengah as many as 22 students who studied with active learning strategies and class V SDN 2 Banjar Tengah 22 students who studied with conventional learning strategies. The data collected in this study was data on students' mathematics learning motivation, which was obtained by using the mathematics learning motivation test, which had a reliability of 0.93. Mathematics learning motivation data were analyzed by descriptive analysis and one-way ANOVA. Hypothesis testing was carried out at a significance level of 5%. The results showed that there were differences in the motivation to learn mathematics between students who studied with active learning strategies and conventional learning strategies (F = 79.93; p <0.05). The results of the LSD test showed that students' motivation to learn mathematics using active learning strategies was higher than conventional learning strategies (LSD = 0.09) ; =0.42).